Earthquake Engineering : Sixth Canadian Conference - Uzumeri, S. M.; Sheikh, Shamim Ahmed, 1950- (Book collections on Project MUSE., 1991)
This conference, along with other similar events throughout the world, has contributed significantly towards understanding various phenomena needed for building safe, reliable, and economical structures that can meet the challenges presented by the forces of nature.